A 5-alkylresorcinol and three3, 4-dihydroisocoumarins derived from Ononis natrix. (September 2015) - Yousaf, Muhammad; Al-Rehaily, Adnan J.; Ahmad, Mohammad S.; Mustafa, Jamal; Al-Yahya, Mohammed A.; Al-Said, Mansour S.; Zhao, Jianping; Khan, Ikhlas A.
Graphical abstract: Highlights: A new alkylresorcinol and three new alkyl isocoumarins were isolated from Ononis natrix . Structures were elucidated on the basis of spectroscopic data. All the compounds were evaluated for their biological activities. Abstract: Phytochemical investigation of Ononis natrix L. led to the isolation of an alkylresorcinol (1 ) and three alkyl isocoumarins (2 –4 ) from the acetonitrile fraction of acetone extract of the aerial part of Ononis natrix. The structures of the compounds were determined by spectroscopic analyses including 1D, 2D NMR, MS, and comparison with literature data. All compounds (1 –4 ) were evaluated for antimicrobial, antiprotozoal, antioxidant and cytotoxic activities. The compounds showed moderate antimicrobial and antiprotozoal activities.